Brill's companion to Silius Italicus - Augoustakis, Antony. (Brill's Companions to Classical Studies., 2010)
Only recently have scholars turned their attention to Silius Italicus' Punica , a poem the reputation of which was eclipsed by the emergence of Virgil's Aeneid as the canonical Latin epos of Augustan Rome. This collection of essays aims at examining the importance of Silius' historical epic in Flavian, Domitianic Rome by offering a detailed overview of the poem's context and intertext, its themes and images, and its reception from antiquity through Renaissance and modern philological criticism. This pioneering volume is the first comprehensive, collaborative study on the longest epic poem in Latin literature.